Defining the capable engineer: Non-technical skills that support safe decisions in uncertain, dynamic situations. (September 2021) - Hayes, Jan; Maslen, Sarah; Holdsworth, Sarah; Sandri, Orana
Highlights: Non-technical skills that support engineers to make safe decisions are critical. The framework addresses 20 capabilities in six groups. Capability groups are linked to sustainability education. Extends individual learning to cover latent error. Abstract: Education and learning are key topics in the safety research literature but the literature focuses primarily on organisational learning from accidents and non-technical skills for those in frontline roles where avoidance of active errors is key. This article addresses the non-technical skills that engineers need in order to make the best long-term choices for public safety while navigating organisational complexity. Previous contributions on engineering education reflect a strong focus on technical competence. Situated in the emerging conversations among education scholars on professional capabilities, we identify the holistic attributes and skills that empower engineers to make the best decisions for safety in uncertain, dynamic situations. Drawing on interviews with 41 engineers in the gas pipeline sector, the analysis develops a framework of individual capabilities for public safety decision-making consisting of 20 core elements. We see these 20 capabilities as falling into six categories: (a) use long-term, foresighted reasoning, especially in the face of uncertainty, (b) understand norms and values that inform actions, (c) think systematically and understand interconnectedness, (d) collaborate with and draw on the experience of others, (e) ground decisions in reality and (f) advocate for action and take responsibility. This capability framework has resonance with comparable work done in the field of sustainability education and extends the safety literature on non-technical skills into a domain where latent errors, rather than active errors, predominate.